An epidemiological investigation of COVID-19 outbreaks in a group of care homes in Wales, UK: a retrospective cohort study. (17th May 2021) - Williams, O; Williams, C; Turner, D; Bull, M; Watkins, J; Hurt, L
Abstract: Background: This study describes the epidemiology of COVID-19 outbreaks in four care homes in terms of spread, severity, presentation and interventions. Methods: Participants were 100 residents and 102 staff from four co-located care homes in Wales. Data were collected from the homes and Public Health Wales, including demographics, presentations, test status and results, hospital admissions and deaths. Genomic sequencing of confirmed case samples was completed, where possible. Epi-curves, crude attack rates, a Kaplan-Meier survival curve and adjusted hazard ratios were calculated using R. Results: About 14 confirmed and 43 possible resident cases, 23 confirmed and 47 possible staff cases occurred. Crude attack rates of possible and confirmed cases were 57% (residents) and 69% (staff). Genomic sequencing for 10 confirmed case PCR samples identified at least 5 different UK lineages of COVID-19.42 (42%) residents died, 23 (55%) with COVID-19 or suspected COVID-19 recorded on the death certificate. The hazard ratio for death amongst resident possible and confirmed cases compared to null cases, adjusting for age and sex, was 13.26 (95% CI 5.61–31.34). Conclusions: There were extensive outbreaks of COVID-19 in these homes with high crude attack rates and deaths. Universal testing and early isolation of residents are recommended.